"Flattery helps": Relational practices in statecraft. (July 2021) - Heimann, Gadi; Kampf, Zohar
Abstract: This paper provides an explanation for how coworkers manage to cultivate close relationships in an extremely competitive workplace. Our case study is the workplace of statespersons, considered an impersonal, rule-governed, and interest-motivated social environment, and as such, provides indications for how counterparts overcome alienation and suspicion in developing trustful relations. Interviews with twenty-one senior Israeli officials concerning mundane professional practices they employed during their service reveal a gamut of relational practices implemented in various formal and informal events in order to initiate, maintain, and strengthen close personal relationship with their foreign counterparts. A competent performance of these practices constitutes meaningful relationships, allowing statespersons to overcome the relational challenges posed by the impersonal diplomatic workplace. Highlights: How to cultivate relations in highly impersonal and interest-oriented workplaces? Statecraft is a challenging arena for developing interpersonal relationships. The study is based on twenty-one interviews with senior Israeli statespersons. Cultivating relations in statecraft is accomplished via verbal and non-verbal practices. Practices are enacted in a variety of settings and have different functions.